Peningkatan Pendapatan Masyarakat Dengan Program Inovasi Desa Melalui Pengolahan Limbah Ikan Curah - Syahrinur Fitriah; Nurida Isnaeni (UNIB Press, 2023)
The purpose of this community service is to test and train the community on the technology of making high protein fish feed pellets from trash fish waste which is useful for reducing the high purchase of fish feed on the market. Therefore, the need for a technology or innovation for the manufacture of fish feed in the community, especially areas where there is fish farming and is expected to reduce the high cost of purchasing feed. The method consists of presentations or training, mentoring and discussions, as well as analysis of business benefits. Members of the catfish breeding partners are mostly aged between 18 to 68 years, have elementary, junior high and high school education. The raw materials for the waste are 5 kg of dry trash fish, 100 g of tapioca flour/0.1 kg, 4.9 kg of rice bran and 1 l of diesel oil and plastic, so you can get up to 8 kg of fish pellets. with the cost required is IDR 39,050 Gross income IDR. 72,000 and a profit of Rp. 32,950. Comparing the benefits and costs incurred is IDR 32,950.00 :I DR 39,050.00 = 0.8 (B/C). Therefore, the fish pellet business is very profitable to develop and can increase the income of the Jati Emas villagers.